Rooftop recipes for relating: Ecologies of humans, animals, and life - Fikry, Noha (AUC Knowledge Fountain, 2019)
This thesis explores the particularly lively rooftops of Cairo through which interspecies intimacies unfold. On these rooftops, various animals (such as chickens, ducks, geese, turkeys, goats, and rabbits) are raised to be later eaten and consumed for sustenance. Throughout the various thesis chapters, I try and expose the various patterned modalities, terms, and codes bringing these different species together in their sustained long-term relationships. I follow these interspecies relations as they narrate wonders of life-and-death, collaborations, various instantiations of home, social gift exchanges, marital rituals, and grieving patterns. These relations involve different tasks, requiring a very specific and complex gendered division of labor, further embedded in broader understandings of home, labor, subsistence, making a living, and growing as properly gendered beings. Rooftop recipes for relating slowly cook these human-nonhuman relations as uniquely embedded in a socio-ecological intricate awareness of surrounding environments of neighbors, families, but also of trees, waste, changing seasons, aging species, and growing parents.